Challenging neonatal central nervous system fungal infection diagnosed by MRI: a case report - Shatrit, Hanin; Deeb, Salahaldeen; Tamimi, Motaz; Smerat, Mohammad I.; Alzatari, Ibrahim (Frontiers in Pediatrics, 2025)
BackgroundAlthough central nervous system fungal infection (CNSF) is uncommon, it is a life-threatening condition that requires prompt diagnosis and management. Here, we report a full-term female neonate with suspected CNSF diagnosed by magnetic resonance imaging (MRI) despite repeatedly negative cerebrospinal fluid (CSF) and blood cultures, in whom the causative pathogen could not be identified.Case presentationA full-term female neonate presented on the first day of life with irritability, hypoactivity, cyanosis, poor feeding, and two episodes of generalized tonic-clonic seizures with up-rolling of the eyes and lip smacking. Workup for neonatal sepsis showed negative CSF and blood cultures. MRI findings suggested CNSF, and treatment was initiated with low-dose conventional amphotericin B deoxycholate (0.5 mg/kg/day) for 4 weeks, leading to complete clinical and radiological resolution.ConclusionNegative CSF and blood cultures do not exclude neonatal CNSF. In resource-limited settings, MRI findings together with clinical response to antifungal therapy may support a diagnosis of probable CNSF, even when the pathogen is not identified and standard high-dose regimens are not available.